Three New Species of Microsphecodes s.str. (Hymenoptera: Halictidae) with an updated key to species of the subgenus - Graham, Liam; Packer, Laurence (Zootaxa, 2024)
We diagnose, describe and illustrate three new species of Microsphecodes Eickwort and Stage, all from the nominate subgenus: M. peckorum Graham and Packer n. sp. from Venezuela, M. fernandoi Graham and Packer n. sp. from French Guiana, and M. septentrionalis Graham and Packer n. sp. from Guatemala. The latter extends the known range of the subgenus further north by approximately 500 km. We provide an updated, illustrated, key to the species of Microsphecodes s.str.